FUNDAMENTALS OF DIGITAL MARKETING - PUNEET SINGH BHATIA (UTTAR PRADESH PEARSON INDIAN EDUCATION SERVICES PVT.LTD, 2023)
Aims At establishing the first steps towards laying the foundational bridge from web 2.0 to web 3.0
FUNDAMENTALS OF DIGITAL MARKETING
management
Keywords: DIGITAL MARKETING; MANAGEMENT